Fine Needle Aspiration (FNA) cytology of the thyroid: A Cyto-Histopathological study of 361 cases in Hospital Universiti Kebangsaan Malaysia - Nurismah MI,; Sharifah NA,; Usama AE,; Naqiyah I,; Rohaizak M,; Jasmi A, (Penerbit UKM, 2007)
Thyroid nodules are common but thyroid malignancies are not. Fine needle aspiration (FNA) cytology is a diagnostic tool used to screen patients with thyroid nodules who require surgery. We study the diagnostic accuracy of FNA as the initial diagnostic modality in the clinical assessment of thyroid nodules. Between January 1995 until December 2000, 2131 FNA of thyroid nodules were performed. Four hundred and forty-one (20.7%) of these were unsatisfactory and 1690 (79.3%) cases were satisfactory for cytological evaluation. Histopathological diagnosis were available for 361 cases. Cyto-histopathological correlation was carried out for these cases. Our results showed a diagnostic accuracy of 96.2% with sensitivity and specificity rates of 87.7% and 98.4% respectively. Our positive predictive value is 93.4% and our negative predictive value is 96.8%. From this study, we conclude that fine needle aspiration is an important initial screening diagnostic tool for the investigation of thyroid nodules